Six Myths About Sports Violence - Mršević, Zorica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
The text is facing six myths (delusions, false statements) about sports violence with the facts that negate them. There are analyzed the following myths: violence and sport "normally" go together; sports violence prevents modern stadiums constructions; in order to suppress fan violence, there should be used the English methods of repression against them; typical fan hooligan is a young man who has trouble with fitting into society; clubs are the main roots of the organized fans hooliganism; a detailed legal regulations of violence in sport and harsher sanctions agains fans are necessary. The author ilustrated her findigs by the extensive media coverage as well as theoretical works. Special attention was given to TV serials "Insider" and "Dossier fan" who publicly presented many unknown facts, pointed to the real root causes of footbal related violence. Also as relevant sources are used experiences of former footbal players themselves, sport sociologist, criminologist and other experts.